(3GdWQjb Edi cQjTfG (B:s (3QMdGJ aj cTejQ hGdgfO (B/s - (3TYdGf, SfGA cGed CMeO,s 1977-; (3GdLQGM, fhQjs ((3CHh XHj (B- (3GdEeGQGJ GdYQHjI GdeJMOI(B:s (3OGQ GdShjOj ddfTQ hGdJhRjY ;s (3HjQhJ (B- (3dHfGf(B:s (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ,s (3YqeGf (B- (3GdCQOf(B:s (3OGQ GdaGQS,s [(3ecGf GdfTQ ZjQ eMOO(B] :s (3GdeQcR GdYQHj ddCOH GdLZQGaj (B((3GQJjGO GdBaGb(B)(3,s, 2023)
(3aj cJGH GdWQjb Edi cQjTfG QMdGJ aj cTejQ hGdgfO, fOQc ce QMdI GdeQCI JJLGhR eLQO NWhGJ aj GdLZQGajG(B. (3agfGc CjVG LQCI aj GdeZGeQI aj YhGde cGfJ JMJcQgG GdQLGd aj GdSGHb(B. (3abO cJH GdQLGd GdeSGaQhf aj gPG GdeLGd CcKQ eeG cJHJ GdeQCI ajg HSHH Jahb GdPchQjI GdJj aJMJ GdBaGb dge(B. (3hdcf GdeQCI bQQJ CNjQG Cf JcJH aj gPG GdeLGd HYjOG Yf bjhO GdCfhKI hJhLjgGJ GdPchQ(B. (3aj cTejQ hGdgfO MjK JJSY GdYjfGf hJaJM GdQhM hJROGO GdJYLH(B.s
(3JUeje GdZdGa (B: (3fGUQ HNjJ ; NWhW GdZdGa (B: (3eMeO fLjH HQHhQ ; GdUa GdVhFj (B: (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ(B.s
Keywords: (3GdTYdGf, SfGA cGed,s -- 1977- -- (3QMdGJs -- (3GdgfOs; (3GdTYdGf, SfGA cGed,s -- 1977- -- (3QMdGJs -- (3cTejQs; (3hUa hQMdGJs -- (3GdgfOs -- (3bQf (B20s